Academic Supervision of Principal of Private Senior High Schools in Bandar Lampung City - Sunarto (CV. Creative Tugu Pena, 2025)
This study aims to describe and analyze the planning, implementation, evaluation, and follow-up of academic supervision conducted by principals at three private Madrasah Aliyah institutions in Bandar Lampung City: MA Darul Falah, MA Hidayatul Islamiyah, and MA TGIA Perkemas. A qualitative descriptive approach with a case study design was employed. Data were collected through observation, interviews, and documentation, and were analyzed using two stages: individual case analysis and cross-case analysis. The primary sources of data included school principals, vice principals, teachers, and administrative staff. The findings reveal the following: First, the principals at all three madrasahs consistently conduct supervision planning by reviewing the completeness of instructional administrative documents, such as syllabi, annual and semester programs, lesson plans (RPP), and minimum mastery criteria (KKM) before classroom instruction. Second, academic supervision is conducted semiannually at MA Darul Falah, while it is conducted annually at MA Hidayatul Islamiyah and MA TGIA Perkemas. Third, the analysis of supervision results involves teachers identifying key issues in the teaching process and implementing improvement programs when students do not meet the minimum performance criteria. Fourth, follow-up actions taken by the principals in academic supervision contribute to the improvement of teacher professionalism, which ultimately supports the achievement of educational objectives. This research emphasizes the importance of structured academic supervision as a strategic tool for improving teaching quality and achieving sustainable educational outcomes in private Islamic schools.